Penyuluhan Perawatan Mandiri Pada Pasien Hipertensi Sebagai Upaya Pengendalian Tekanan Darah - Mechi Silvia Dora; Wahyuni Anwar; Andi Arfah; Fitriani.K Fitriani.K; Arnes Yuli Vandika (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Hypertension is one of the most prevalent non-communicable diseases in Indonesia and a major risk factor for various cardiovascular complications. Low knowledge and awareness about self-care among patients contribute to the high rate of uncontrolled hypertension cases. This community service activity aims to improve the knowledge and ability of hypertensive patients in performing self-care as an effort to control blood pressure. The activity was conducted by lecturers through lectures, discussions, demonstrations, distribution of educational leaflets, and blood pressure monitoring. The target participants were 25 hypertensive patients aged 40–50 years. Evaluation results showed an 80% increase in participants’ understanding based on pre–post test questionnaires. This activity demonstrates that proper education and assistance can enhance patients’ self-care ability in managing hypertension and potentially reduce the risk of complications.